A rare case of the late onset of Balo concentric sclerosis - V. A. Shidlovsky; E. A. Gorkova; A. A. Yakovlev; T. V. Lalayan; A. G. Smochilin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
Balo concentric sclerosis is considered a fulminant demyelinating disease that is characterized by the formation of specific concentric foci in the white matter of the brain that resemble sawing trees. This article describes the clinical case of a patient who has come with complaints of weakness and stiffness in the lower limbs, more in the left leg, a feeling of stiffness and tension in the left hand, the inability to walk without aids. Taking into account the complaints, the clinical picture and the pre-test: laboratory examination of blood and liquor, magnetic resonance imaging (MRI) of the brain and thoracic spine with contrast, the patient was diagnosed with multiple sclerosis, secondary-spineprogressive current (Balo variant), reliable according to the 2017 McDonald Criteria. The following is a literature review describing the pathogenesis, clinical profile, diagnostic approaches and treatment options for the disease.